English Proficiency of Students at Politeknik Negeri Balikpapan Based on TOEIC - Lilik Damayanti; Abdul Gafur (Universitas Teknokrat Indonesia, 2020)
English language proficiency is generally measured by English competency scores such as TOEFL and TOEIC. To be able to apply the right learning patterns for students of Politeknik Negeri Balikpapan (Poltekba) for the purpose of mastering the TOEIC, an analysis of their English proficiency is needed by measuring their TOEIC scores. This analysis can be used as a reference for English lecturers in providing relevant learning materials according to the needs of the students and the industrial world. The research method used is qualitative-quantitative because it focuses on analyzing the TOEIC scores of the students. The researchers conducted analysis on the TOEIC scores as the data and explained them descriptively. The data used in this analysis are TOEIC scores from 291 students. The scores were mapped into 6 levels of English proficiency. The results of this study describe the level of English proficiency and the comparison between mastering Listening and Reading Comprehensions by the students at Politeknik Negeri Balikpapan.